2017
DOI: 10.2503/hortj.mi-094
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Cultivar Differences in Plant Regeneration Ability in an Apple Anther Culture

Abstract: To select cultivars to produce doubled haploids (DHs) efficiently in an anther culture, a total of 28 apple cultivars (25 cultivars and 3 rootstock cultivars) were investigated to assess their callus formation rate, embryo formation rate, shoot formation rate from embryo, and efficiency of shoot multiplication and acclimatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The data for 'ASP', 'Senshu' and'SD' from 2009-2011 are shown in a previous report (Zhang et al, 2017). 'ASP' showed the highest embryo formation rate, with an average rate over three years of 14.4%.…”
Section: Embryos and Callus Formation From Anther Culturesmentioning
confidence: 83%
See 4 more Smart Citations
“…The data for 'ASP', 'Senshu' and'SD' from 2009-2011 are shown in a previous report (Zhang et al, 2017). 'ASP' showed the highest embryo formation rate, with an average rate over three years of 14.4%.…”
Section: Embryos and Callus Formation From Anther Culturesmentioning
confidence: 83%
“…In our previous experiments (Zhang et al, 2013(Zhang et al, , 2017, the ability to induce embryos from anthers depended mostly on the applied cultivar. This study revealed that the genotypes also played an important role in the process of plant regeneration from apple anther culture-derived embryos.…”
Section: Effects Of Genotypes On Shoot Regenerationmentioning
confidence: 95%
See 3 more Smart Citations